Social protection in the eye of hurricane: counter-reforms in Latin America - Diehl, Rodrigo Cristiano; Mendes, Jussara Maria Rosa (Argumentum, 2020)
This study aims to understand the main elements (political, economic, and social) present in the reform and counter-reform processes of social protection systems in Latin America. The methodology was exploratory-descriptive, quantitative, and qualitative bibliographic research and using dialectical materialism as a method and pathway for knowledge production. The study starts from the following question: what are the main elements present in the reform and counter-reform processes in social protection systems in Latin America? Among the main conclusions, we highlight the similarity in structural counter-reforms regarding the need to meet the new capital requirements, which requires the support of multilateral agencies and reduced social spending to enable new conditions for the free movement of capital and increased profits.